THE GENEALOGY OF SANTREN AS IDEOLOGICAL BASIS OF RESISTENCE MOVEMENT OF SASAK SOCIETY AGAINST COLONIALISM IN LOMBOK - Rahim, Abdul; Zaynassyakur, Muhammad Yazid; Halimatuzzahro, Halimatuzzahro (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
Santren is the name of a place that has been used as a center for religious teaching in Sasak society for a long time. This article critiques the contemporary lack of attention toward Santren as the earliest institution for Islamic education among the Sasak people. Furthermore, it explores the genealogy of Santren as a space for mental and spiritual cultivation since Islam became the official religion of the Selaparang kingdom.. Based on the theoretical basis of genealogy from Michel Foucault, this research was conducted by exploring historical data, criticizing phenomena and reality, with a new ethnographic approach in the form of self-reflexifity and truthfulness. The results of the author's findings revealed that the genealogy of Santren as a place of religious teaching was practiced from the early Islamic era in the Kingdom of Selaparang that receive Islam as the religion of Sasak community. Then, when the troops of Karangasem Kingdom, Bali reached the Kingdom of Selaparang, Santren turned in the basis of resistence, and also against Dutch, and Japan in colonialism era which centered in guru ngaji (qur’anic teachers) as the actor. Then, after the Independence of Indonesia, form of resistence transform against ignorance, backwardness, and poverty.